SEORANG PENDERITA DENGAN KARSINOMA SEL SKUAMUS ESOFAGUS - Arsana, I Putu; Wibawa, I Dewa Nyoman (journal of internal medicine, 2012)
Oesophageal carcinoma still rare in Indonesia. Several centers reported low prevalence of oesophageal carcinoma. Three patients found in Palembang in one year, while four patients found in Bandung within ! ve years. Esophageal carcinoma was found in 1.1% of all cancer, and 7% of all digestive organ cancers in United States. Oesophageal carcinoma have mortality ratio of 0.95%. Oesophageal carcinoma more frequent in men with a ratio of 3:1. Diagnosis by anamnesis, physical examination, routine blood tests, barium esophagogram, esofago-gastroduodenoscopy, chest and abdominal CT-scan or MRI, bronchoscopy, endoscopic ultrasound, and also with laparoscopy. A 55-years old Balinese woman came with complaints of dif! culty in swallowing and diagnosed as squamous cell middle third oesophageal carcinoma stage III. Anamnesis, barium esofagogram, gastroduodenum endoscopy (OGD), and histopathological biopsy con! rmed the diagnosis of this patient. This patient given chemotherapy with combination of 5-" uorouracil (5-FU) 40 mg/day and cisplatin 1500 mg/day 2 ? 3 cycles every 3 weeks
Keywords: Oesophageal carcinoma, non-keratinizing squamous cell carcinoma